Design of an offshore three-bladed vertical axis wind turbine for wind tunnel experiments - Roy, Sukanta; Branger, H.; Luneau, C.; Bourras, D.; Paillard, B. (2017)
© 2017 ASME. The rapid shrinkage of fossil fuel sources and contrary fast-growing energy needs of social, industrial and technological enhancements, necessitate the need of different approaches to exploit the various renewable energy sources. Among the several technological alternatives, wind energy is one of the most emerging prospective because of its renewable, sustainable and environment friendly nature, especially at its offshore locations. The recent growth of the offshore wind energy market has significantly increased the technological importance of the offshore vertical axis wind turbines, both as floating or fixed installations. Particularly, the class of liftdriven vertical axis wind turbines is very promising; however, the existing design and technology is not competent enough to meet the global need of offshore wind energy. In this context, the project AEROPITCH co-investigated by EOLFI, CORETI and IRPHE aims at the development of a robust and sophisticated offshore vertical axis wind turbine, which would bring decisive competitive advantage in the offshore wind energy market. In this paper, simulations have been performed on the various airfoils of NACA 4-series, 5-series and Selig profiles at different chord Reynolds numbers of 60000, 100000 and 140000 using double multiple streamtube model with tip loss correction. Based on the power coefficient, the best suitable airfoil S1046 has been selected for a 3-bladed vertical axis wind turbine. Besides the blade profile, the turbine design parameters such as aspect ratio and solidity ratio have also been investigated by varying the diameter and chord of the blade. Further, a series of wind tunnel experiments will be performed on the developed wind turbine, and the implementation of active pitch control in the developed turbine will be investigated in future research.